Spatio-temporal determinants of income inequality in the cantons of Ecuador between 2010 and 2019: An econometric analysis for spatial panel - Quito, Byron (2021)
In Ecuador, according to Garzón et al. (2016) in the 2010-2013 period, the average annual birth rate of companies in this sector was 18.7% and the mortality rate (closing) was 8.7%, which means that, during this period, approximately 500 companies Manufacturing companies closed each year, which led to hundreds of lost jobs and families without resources from the sources of employment provided by this sector. The study of bankruptcy of companies in the manufacturing sector is pertinent since according to figures from the Central Bank of Ecuador (BCE), for the period 2013-2018 the manufacturing industry has an average participation of 14.09% of annual GDP, being one of the main industries productive followed by construction and commerce that have a participation of 11.95% and 10.60%, respectively. According to data from the Superintendency of Companies, by 2018 the "Manufacturing Industries" sector had 6,003 companies, generating a considerable amount of employed personnel that amounts to 319,029. Based on the aforementioned, it is necessary to develop and implement prevention tools on a possible business bankruptcy. Therefore, this study's main objective is to identify and analyze the business factors that increase or reduce the risk of bankruptcy of companies in the manufacturing sector in Ecuador.